An online innovation platform to promote collaboration and sustainability in short food supply chains - Foteini Chrysanthopoulou; Marieke Lameris; Gunter Greil; Dusan Vudragovic; Katherine Flynn (International Journal of Food Studies, 2022)
A sustainable Short Food Supply Chain (SFSC) requires collaboration among all actors, which nowadays is facilitated by information and communication technologies (ICT). However, not all SFSC stakeholders network with others in this way, and it is not clear what will draw them to ICT interaction. A simple, user-friendly website, the SMARTCHAIN Innovation Platform, evolving since March 2019, may facilitate interaction and cooperation among SFSC stakeholders. This article presents the Platform's development and evaluates its efficacy and impact by analysing data from Google Analytics (GA) and other sources. Primary Platform features promote communication and information sharing: these are the 1) Innovation Hubs in 9 European countries, 2) Inventories including 150 SFSC innovations and 50 SFSC initiatives, 3) Resources databases of Publications and Weblinks, and 4) Training section. GA showed that visitors to the Platform increased slowly in the 16 months since its start, and the number of page views increased with the amount of time on the Platform. The most visited page of the Platform was the information-providing Innovation Inventory. Most Platform users were in partner countries of the SMARTCHAIN project, but not all Innovation Hubs had high numbers of users. Most users arrived at the Platform by direct link, but LinkedIn was the most important originating social network. Taken together, these data suggest growth potential for an easy-to-use website that provides useful and up-to-date information but little inclination for SFSC stakeholders to use an online Platform for communication.